THE RELATIONSHIP OF BIRTH WEIGHT (BBL) AND PROVIDING COMPLEMENTARY FEEDING AMONG THE INCIDENCE OF STUNTING: HUBUNGAN BERAT BAYI LAHIR (BBL) DAN PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) DENGAN KEJADIAN STUNTING PADA BALITA - Mulyani, Siti; Hanifatun Fajria, Siti; Irawan, Devi (Jurnal Ilmiah Wijaya, 2020)
Background of Study: Toddlers are included in the nutritionally vulnerable society groups. An example of growth disorders is stunting. Stunting is a growth disorder in toddlers due to chronic malnutrition with TB/U index. If the z-score <-2 SD, then it is categorized as stunted and severely stunted if the z-score <-3 SD. Data from Riskesdas 2018 showed that the incidence of toddler stunting was 30.8%. Objective: Analyze the relationship between birth weight and giving complementary feeding with the incidence of toddler stunting.Method: This research used descriptive analytical study with cross sectional design. Thepopulation consists of mothers with stunted toddler and the sample obtained consisted of 122 respondents. This research was done on August 2019 at Cibungbulang Public Health Center. The bivariate analysis used chi-square test, whereas the multivariate analysis used double logistic regression test. Result : The results from the bivariate analysis indicated there was a significant relationship between birth weight (p=0.002) with the incidence of stunting and an insignificant relationship was deduced between giving complementary feeding (p=0.11) with the incidence of toddler stunting. The results of multivariate analysis showed that birth weight was the dominant risk factor of toddler stunting. Toddlers with normal birth weight had a risk rate of 3.79 times of stunting with stunted category, while giving complementary feeding was a confounding variable, thus it must be controlled.Conclusion: This research showed that there was a significant relationship between birthweight with the incidence of toddler stunting, whereas there was an insignificant relationship between giving complementary feeding with the incidence of toddler stunting. Suggestion: This research is expected to be a feedback for Cibungbulang Public Health Center as a means for prevention and early detection of toddler stunting.